Evidence-informed guidelines in oral health: insights from a systematic survey - Francisca Verdugo-Paiva; Ana María Rojas-Gómez; Vicente Wielandt; Javiera Peña; Iván Silva-Ruz; Francisco Novillo; Camila Ávila-Oliver; Xavier Bonfill-Cosp; Michael Glick; Alonso Carrasco-Labra (BMC, 2024)
Abstract Background Oral diseases are a major global public health problem, impacting the quality of life of those affected. While consensus exists on the importance of high-quality, evidence-informed guidelines to inform practice and public health decisions in medicine, appropriate methodologies and standards are not commonly adhered to among producers of oral health guidelines. This study aimed to systematically identify organizations that develop evidence-informed guidelines in oral health globally and survey the methodological process followed to formulate recommendations. Methods We searched numerous electronic databases, guideline repositories, and websites of guideline developers, scientific societies, and international organizations (January 2012-October 2023) to identify organizations that develop guidelines addressing any oral health topic and that explicitly declare the inclusion of research evidence in their development. Pairs of reviewers independently evaluated potentially eligible organizations according to predefined selection criteria and extracted data about the organization's characteristics, key features of their guidelines, and the process followed when formulating formal recommendations. Descriptive statistics were used to analyze and summarize data. Results We included 46 organizations that developed evidence-informed guidelines in oral health. The organizations were mainly professional associations and scientific societies (67%), followed by governmental organizations (28%). In total, organizations produced 55 different guideline document types, most of them containing recommendations for clinical practice (77%). Panels were primarily composed of healthcare professionals (87%), followed by research methodologists (40%), policymakers (24%), and patient partners (18%). Most (60%) of the guidelines reported their funding source, but only one out of three (33%) included a conflict of interest (COI) policy management. The methodology used in the 55 guideline document types varied across the organizations, but only 19 (35%) contained formal recommendations. Half (51%) of the guideline documents referred to a methodology handbook, 46% suggested a structured approach or system for rating the certainty of the evidence and the strength of recommendations, and 37% mentioned using a framework to move from evidence to decisions, with the GRADE-EtD being the most widely used (27%). Conclusion Our findings underscore the need for alignment and standardization of both terminology and methodologies used in oral health guidelines with current international standards to formulate trustworthy recommendations.